Rekrutmen dan Pemeliharaan (Maintenance) Karyawan Disabilitas dalam Perspektif Manajemen Sumber Daya Insani - Khozainul Ulum; Mohammad Dliyaul Muflihin (Universitas Islam Lamongan, 2020)
Abstract: The recruitment and maintenance of employee with disabilities should be handled by company in harmonic context. This research aims at revealing how the recruitment and maintenance for the employees with disabilities practically carried by the company. Qualitative method is applied in this research, while the data are taken from relevant literary sources under the theme of recruitment and maintenance of employees with disabilities. The data, than, are analyzed using descriptive analysis. The findings suggest several points. First, recruitment is the process of searching, recruiting, and finding the competent and reliable employee candidates to deal with certain division, even if they have such disabilities. Being selective while choosing the right candidate is really the crucial key point since all the candidates are competent, smart, responsible, reliable, and expert in their jobs. Second, after obtaining the appropriate candidate, the maintenance toward the employees with disabilities is really a must do. The maintenance can be done by settling the policy of disability, twining the relationship and consulting with organization of employee with disability, adjusting the workplace, and raising awareness of the employees. Keywords: recruitment and maintenance; employee with disability; management of human resources